Quality of life in patients with type II diabetes - Rezvan Ghafarzadegan; Daryadokht Masror; soror Parvizy; Mohammad Ebrahim Khamse; Hamid Haghani (Payesh, 2013)
Objective (s): Diabetes is one of the most common metabolic syndromes with debilitating complication, and chronic course. Chronic complications of diabetes and its potential costs are often causing of financial loss and decrease of quality of life. This study aimed to assess quality of life and its dimensions in patients with type II diabetes. Methods: This was a cross-sectional study of 224 patients with Type II diabetes referred to the Endocrinology and Metabolism Institute of Iran University of Medical Sciences. Data were collected on demographic and quality of life including information on 5 dimensions (physical, psychological, social, economic and disease and treatment). Results: The results showed that the physical quality of life in 53.3 percent of sample was more than average score. Also 63.4% of the patients scored higher than mean score on psychological dimension. This figure for social, economic and disease and treatment related dimensions were 65.4%, 51.8% and 51.4% respectively. Quality of life significantly was associated with age, gender, educational level, economic status and complications.Conclusion: The findings confirmed that quality of life in diabetic patients was associated with demographic factors. Indeed in order to better manage patients subgroup of patients should be considered.|